2015
DOI: 10.1111/bjd.13277
|View full text |Cite
|
Sign up to set email alerts
|

Addition of an oral histamine antagonist to reduce adverse events associated with fumaric acid esters in the treatment of psoriasis: a randomized double-blind placebo-controlled trial

Abstract: Addition of oral cetirizine 10 mg once daily to FAE treatment did not reduce adverse events in patients with psoriasis during the first 12 weeks of treatment. The mechanisms underlying FAE-induced gastrointestinal and flushing symptoms likely involve mediators other than histamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The placebo‐controlled RCT for the treatment of psoriatic arthritis using FAEs found significant improvement in skin lesions but only modest improvement in arthritis . Only one RCT reported improvements in health‐related quality of life following treatment with FAEs …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The placebo‐controlled RCT for the treatment of psoriatic arthritis using FAEs found significant improvement in skin lesions but only modest improvement in arthritis . Only one RCT reported improvements in health‐related quality of life following treatment with FAEs …”
Section: Resultsmentioning
confidence: 99%
“…The addition of a topical vitamin D analogue (calcipotriol) resulted in greater and faster improvement of psoriasis severity compared with treatment using FAEs alone . In contrast, the addition of an oral histamine‐1 receptor antagonist (cetirizine) did not increase the efficacy of FAEs …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 11 potentially eligible studies were identified after screening the titles and abstracts. After reading the full texts, five articles were excluded due to failure to meet our prespecified inclusion criteria [11][12][13][14] and lack of evidence of randomization. 15 As a result, six studies with a total of 544 participants were included in our review; five compared FAE with placebo [16][17][18][19][20] and one used methotrexate as an active comparator.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%